Evaluation of the single radial haemolysis (SRH) technique for rubella antibody measurement. Issue 6 (June 1978) - Russell, S M; Benjamin, S R; Briggs, M; Jenkins, M; Mortimer, P P; Payne, S B
Abstract : Sera from 1258 individuals have been tested by four laboratories for rubella antibody by both the haemagglutination-inhibition and single radial haemolysis techniques. There was good agreement between the results obtained by the two methods. Although sheep red blood cells were used in the single radial haemolysis plates, no problems were encountered with sera from patients with infectious mononucleosis. The single haemolysis technique was found to be simple, convenient, and reliable, and suited to the rapid screening of large numbers of sera to assess susceptibility to rubella in the context of a vaccination campaign. However, since the technique does not detect anti-rubella IgM, it should not be used as the only test to investigate suspected recent infection.